PBTK modeled perfluoroalkyl acid kinetics in zebrafish eleutheroembryos suggests impacts on bioconcentrations by chorion porosity dynamics. (June 2023) - Billat, Pierre-André; Vogs, Carolina; Blassiau, Clément; Brochot, Céline; Wincent, Emma; Brion, François; Beaudouin, Rémy
Abstract: The zebrafish eleutheroembryo ( zfe ) is widely used as a model to characterize the toxicity of chemicals. However, analytical methods are still missing to measure organ concentrations. Therefore, physiologically-based toxicokinetic (PBTK) modeling may overcome current limitations to help understand the relationship between toxic effects and internal exposure in various organs. A previous PBTK model has been updated to include the chorionic transport barrier and its permeabilization, hatching dynamics within a zfe population over development, and active mediated transport mechanisms. The zfe PBTK model has been calibrated using measured time-dependent internal concentrations of PFBA, PFHxS, PFOA, and PFOS in a zfe population and evaluated using external datasets from the literature. Calibration was successful with 96% of the predictions falling within a 2-fold range of the observed concentrations. The external dataset was correctly estimated with about 50% of the predictions falling within a factor of 3 of the observed data and 10% of the predictions are out of the 10-fold error. The calibrated model suggested that active mediated transport differs between PFAS with a sulfonic and carboxylic acid functional end groups. This PBTK model predicts well the fate of PFAS with various physicochemical properties in zfe. Therefore, this model may improve the use of zfe as an alternative model in toxicokinetic-toxicodynamic studies and help to refine and reduce zfe-based experiments, while giving insights into the internal kinetics of chemicals. Highlights: Exploration of the kinetics of PFBA, PFOA, PFHxS, and PFOS in zebrafish embryos. Model considering the influence of hatching dynamics within an embryos' population. Active transport may differ between PFAS with various functional end groups. New tool to evaluate the impact of hatching delay on chemical internal dose.